2012
DOI: 10.2319/111911-716.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different intracoronal bleaching methods on shear bond strengths of orthodontic brackets

Abstract: Objective: To evaluate the effects of different intracoronal bleaching methods on the shear bond strengths (SBS) of orthodontic brackets. Materials and Methods: Sixty freshly extracted mandibular incisors were randomly divided into four groups (n 5 15 per group). After filling the root canals, root fillings were removed 2 mm apical to the cementoenamel junction, and a 2-mm-thick layer of zinc-phosphate cement base was applied. Group 1 served as the control. Intracoronal bleaching was performed with hydrogen pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…The effect of sodium perborate was evaluated during intracoronal bleaching on the SBS values of metallic brackets. 21 Non-vital bleaching with sodium perborate mixed with 30% hydrogen peroxide affected the resin/enamel SBS values. 22 Similarly, Shinohara et al 23 reported that non-vital bleaching treatment with sodium perborate and distilled water adversely affected the SBS of composite resin for both enamel and dentin.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sodium perborate was evaluated during intracoronal bleaching on the SBS values of metallic brackets. 21 Non-vital bleaching with sodium perborate mixed with 30% hydrogen peroxide affected the resin/enamel SBS values. 22 Similarly, Shinohara et al 23 reported that non-vital bleaching treatment with sodium perborate and distilled water adversely affected the SBS of composite resin for both enamel and dentin.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results have been reported previously in the literature. 15 Influence of intracoronal bleaching agents and protocols on the shear bond strength of orthodontic brackets was assessed by Gungor et al 3 They evaluated 60 freshly extracted mandibular incisors and divided them randomly into four study groups with 15 specimens in each group. After performing root canal therapy in each group, they removed the fillings from 2 mm short of apex till cementoenamel junction and applied zinc phosphate base.…”
Section: Discussionmentioning
confidence: 99%
“…It has numerous complex etiologic components that are normally categorized into intrinsic and extrinsic. [1][2][3] Two ways of tooth bleaching are available these days, which includes in-office bleach and home bleach. For the past many years, in-office bleach is being used in dentistry.…”
Section: Introductionmentioning
confidence: 99%
“…1 With an increasing demand for adult orthodontics, orthodontists often encounter patients who are unsatisfied not only with the alignment but also with the color of their teeth. 1 Bleaching with various whitening agents in the office and in the home has now gained worldwide acceptance and has become popular among clinicians and patients as a method for lightening teeth. However, the changes in enamel structure and composition induced by these bleaching agents may decrease the shear bond strength (SBS) of orthodontic brackets.…”
Section: Introductionmentioning
confidence: 99%
“…3 Today, the most commonly used tooth bleaching agents contain hydrogen peroxide as the active ingredient. 1 Hydrogen peroxide may be applied directly or produced by a chemical reaction from sodium perborate or carbamide peroxide. 3 Hydrogen peroxide acts as a strong oxidizing agent through the formation of reactive oxygen molecules; these reactive molecules attack long-chained, darkcolored chromophore molecules and split them into smaller, less colored, and more diffusible molecules.…”
Section: Introductionmentioning
confidence: 99%